The use of the image analysis method for the segregation of shredded waste in an air classifier = Wykorzystanie metod analizy obrazu do segregacji odpadów rozdrobnionych w klasyfikatorze pneumatycznym - Zagaj, Irmina; Ulbrich, Roman (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Segregation of shredded waste is one of the technologies of waste management, along with issues related to manual segregation, while nowadays it starts to be associated with pneumatic classification. This paper discusses the use of an air classifier and image analysis techniques for the purposes of evaluation of segregation of shredded waste. This type of air classifier plays an important role due to the efficiency of the device and the characteristics of segregation. The authors report the results of research into image analysis of segregation of shredded waste on the basis of the use of image analysis.
Keywords: segregacja; odpady rozdrobnione; klasyfikator pneumatyczny; metoda analizy obrazu; segregation; shredded waste; air classifier; image analysis method